Preparation and characterization of electrical properties of graphene oxide (GO)/epoxy composites - Abdullah S.I.; Ansari M.N.M. (Elsevier Ltd, 2023)
Electric conductivity; Epoxy resins; Graphene; Scanning electron microscopy; Conductivity; Electrical conductivity; Epoxy; Epoxy composite; Graphene oxides; Oxide contents; Pure epoxy; Epoxy composites